Prediction of Height from Various Limb Measurement - Syafira, Aisha Dinda; Huspa, Fitri Agustina; Wahyudi, Kurnia (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Height has an important role in forensic medicine and clinical context, namely for biological profile identification of missing or unknown individuals and to provide an easier way to assess nutritional status of bedridden patients or elderly. This literature review aims to explore the variations in height prediction formulas based on limb bone length and to identify the advantages and limitations of these prediction techniques. Scientific studies were selected from Google Scholar, Scopus, and PubMed. Boolean operators and filters were applied to limit only relevant studies. The inclusion criteria in this research are research published in journals in the period 2019-2024, in the form of articles and not pre-prints, in Indonesian or English, research conducted on living humans, full research access-text and free. The exclusion criteria in this research are child and elderly research participants, research participants who suffer from certain diseases, and research using supporting examinations or artificial intelligence. These studies were then selected by using PRISMA flow. 30 articles were included in this study from 367 results. Most of the studies show that there is a positive correlation between stature and limb bone length. Therefore, height can be predicted by limb bone length but should consider population variations such as age, gender, ethnicity, nutritional status, and medical conditions. Keywords: stature, estimation, prediction, limb bone length